Adoption of Foreign Technologies in Korean Manufacturing Firms: Characteristics and Microfoundations - Joong hae Suh (KDI Journal of Economic Policy, 2015)
The primary goal of this paper is to explore the microeconomic foundation of Korean firms' adoption of foreign technologies. The paper also reviews the overall trend of international technology transfers to Korea. The period covered in this paper is Korea's high growth era, from the 1960s to the 1990s. The works of this paper center on the two questions of what characterizes foreign technologies which had been imported through licensing contracts, and which driving forces expedite technology adoption by firms. The Korean experience provides the context of success in the catch-up growth. The co-movement of technology imports with capital goods imports manifests Korea's effort to improve the technical efficiency toward the world frontier. Underlying this trend are firms' decisions to adopt new technologies. The paper shows that firms respond proactively to wage increases by adopting newer technologies and thus, in turn, increasing employment, which implies the existence of a virtuous interactive mechanism among these factors.
Keywords: O12; O14; O33; 330; Korean manufacturing firms; catchup growth; international technology transfer; technology adoption; microeconomic analysis of economic development